How to cheat at securing your network - Dubrawsky, Ido. (Burlington, MA : Syngress, 2007)
Most System Administrators are not security specialists. Keeping the network secure is one of many responsibilities, and it is usually not a priority until disaster strikes. How to Cheat at Securing Your Network is the perfect book for this audience. The book takes the huge amount of information available on network security and distils it into concise recommendations and instructions, using real-world, step-by-step instruction. The latest addition to the bestselling "How to Cheat ..." series of IT handbooks, this book clearly identifies the primary vulnerabilities of most computer networks, including user access, remote access, messaging, wireless hacking, media, email threats, storage devices, and web applications. Solutions are provided for each type of threat, with emphasis on intrusion detection, prevention, and disaster recovery. .Get an Introduction to AAA See how AAA is made up of three distinct but interdependent parts: access control, authentication, and auditing. .Understand the Types of Attacks Learn about active attacks: network-based, application-based, and mixed threat, as well as passive attacks, password attacks, and code attacks. .Address Remote Access Problems Technologies such as RAS servers, NAS, VPN, authentication servers like RADIUS, TACACS, and TACACS+, and others were designed to address the RAS problems. .Review Wireless Technologies Understand WAP and IEEE 802/11 WLAN wireless security methods. .Web Servers are Critical Network Components Make sure that they are as safe as possible and know the issues regarding Web services. .Know the Differences Between Device-Based and Media-Based Security See how wireless, modems, RAS, PBXs, and VPNs allow remote access to a computer or network. .See the Concepts and Processes of OS and NOS Hardening Track, evaluate, and install the appropriate OS patches, updates, service packs, and hotfixes in your system environment. .Understand the Basics of Cryptography See how confidentiality, integrit.
Statement of responsibility from cover.
Includes index.
Keywords: Computer networks -- Security measures; Computer security; Electronic books